A Case of Severe Corneal Flattening after Descemet Stripping Endothelial Keratoplasty. Issue 1 (January 2016) - Fernández-López, Ester; Miron, Alina; Pogorelova, Svetlana; Oganesyan, Oganes; Baydoun, Lamis; Melles, Gerrit R.J.
Purpose: To report a case of extreme corneal flattening after initially uneventful Descemet stripping endothelial keratoplasty (DSEK). Methods: A 76-year-old man underwent uneventful DSEK for pseudophakic bullous keratopathy (PBK) in his left eye. Postoperative evaluations were performed using anterior segment optical coherence tomography and biomicroscopy. Results: The DSEK graft showed full adherence to the host stroma. Two weeks after surgery, the transplanted cornea developed pronounced flattening of the central corneal curvature accompanied by graft folds and remained unchanged until the most recent follow-up 20 weeks after surgery. Conclusions: Severe corneal flattening may be an undescribed complication occurring after uneventful DSEK, without any concomitant ocular pathology or detectable cause.